2008
DOI: 10.3109/2000-1967-211
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Investigation of the Antibacterial Effect of Ketamine

Abstract: Background: Antibacterial activity of local anesthetics especially lidocaine has been shown previously. In this study, the antibacterial effect of ketamine, a general anesthetic agent was investigated. Methods:The antibacterial effect of ketamine was studied using six different strains of bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Entecoccus faecalis, Streptococcus pyogenes, Pseudomonas aeruginosa and Escherichia coli) with disc diffusion method. Ciprofloxacine discs (CIP, oxoid) were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…Gocmen et al investigated the antimicrobial activity of ketamine on S.aureus, S.epidermidis, E.faecalis, S.pyogenes, S.aeruginosa and E.coli by using disc diffusion method. They determined that discs containing 500 and 250 μg of ketamine were as effective as ciprofloxacin and inhibited bacterial growth, discs containing 125 μg of ketamine had antimicrobial activity against other bacteria except for E.coli, and discs containing 6.25 μg of ketamine did not exhibit any antimicrobial activity (19). In this study, similar to our results, ketamine showed antimicrobial activity.…”
Section: Discussionsupporting
confidence: 89%
“…Gocmen et al investigated the antimicrobial activity of ketamine on S.aureus, S.epidermidis, E.faecalis, S.pyogenes, S.aeruginosa and E.coli by using disc diffusion method. They determined that discs containing 500 and 250 μg of ketamine were as effective as ciprofloxacin and inhibited bacterial growth, discs containing 125 μg of ketamine had antimicrobial activity against other bacteria except for E.coli, and discs containing 6.25 μg of ketamine did not exhibit any antimicrobial activity (19). In this study, similar to our results, ketamine showed antimicrobial activity.…”
Section: Discussionsupporting
confidence: 89%
“…Although their antimicrobial mechanism of action has not been completely clarified yet, studies in recent decades have demonstrated that LAs have a wide spectrum of antimicrobial effects . It is reported that LAs inhibit the growth of live bacteria, reduce the membrane‐dependent enzymatic activity of living cells, cause lysis in protoplasts, change the membrane permeability, and lead to ultrastructural alterations; however, these findings have not been completely established …”
Section: Introductionmentioning
confidence: 99%
“…and Candida albicans Mandal et al 2010In vivoAt doses of 25 μg/g and 30 μg/g significantly protects mice from Salmonella typhimurium Mandal et al 2010ClomipramineIn vitroCytotoxic effects against both human protozoan parasites Leishmania donovani and Leishmania major Zilberstein and Dwyer 1984DesipramineIn vitroEffective against Plasmodium falciparum Basco and Le Bras 1990; Salama and Facer 1990EscitalopramIn vitroAntimicrobial effect on E. coli , but no effect on L. rhamnosus Cussotto et al 2018FluoxetineIn vitroStrong dose-dependent antimicrobial activity against L. rhamnosus and E. coli Cussotto et al 2018In vivo4-week administration in rats completely inhibits the growth of Succinivibrio and Prevotella caecal taxaCussotto et al 2018ImipramineIn vitroCytotoxic effects against both human protozoan parasites Leishmania donovani and Leishmania major Zilberstein and Dwyer 1984Inhibits the growth of E. coli and Yersinia enterocolitica through interference with plasmid replication. It also inhibits the parasite Giardia lamblia Csiszar and Molnar 1992; Molnar 1988; Weinbach et al 1992KetamineIn vitroAntimicrobial activity against: S. aureus , S. epidermidis , E. faecalis , S. pyogenes , P. aeruginosa and E. coli , with S. aureus and S. pyogenes being the most sensitive strainsBegec et al 2013; Gocmen et al 2008Sustained antimicrobial activity in a dose-dependent manner against microorganisms in propofol, which is a strong growth-promoting factorBegec et al 2013PromethazineIn vitroInhibits the growth of E. coli and Yersinia enterocolitica through interference with plasmid replicationCsiszar and Molnar 1992; Molnar 1988SertralineIn vitroPotent antimicrobial against E. coli Bohnert et al 2011Inhibits the growth of S. aureus , E. coli and P. aeruginosa and also shows synergy in combination with antibioticsAyaz et al 2015Potent antifungal activity against Cryptococcus neoformans , Coccidioides immitis and Candida spp.Rossato et al 2016; Trevino-Rangel Rde et al 2016…”
Section: The Gut Microbiota Affects the Pharmacokinetics Of Drugsmentioning
confidence: 99%